2013
DOI: 10.1016/j.ramb.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent fasting on metabolism in men

Abstract: This review analyzes the available literature on the impact of intermittent fasting (IF), a nutritional intervention, on different aspects of metabolism. The epidemic of metabolic disturbances, such as obesity, metabolic syndrome (MS), and diabetes mellitus type 2 has led to an increase in the prevalence of cardiovascular diseases, and affected patients might significantly benefit from modifications in nutritional habits. Recent experimental studies have elucidated some of the metabolic mechanisms involved wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 44 publications
1
34
0
10
Order By: Relevance
“…Thus, approaches targeting the cause rather than the symptoms of nutrient overload should yield more desirable outcomes. Moving beyond the standard recommendation to “eat less and move more,” recent studies employing unconventional behavior modification interventions have produced intriguing results, including intermittent fasting regimens in which rodents or human subjects fast for extended periods followed by ad libitum eating (Azevedo et al, 2013; Trepanowski et al, 2011), as well as “exercise snacking” regimens in which individuals exercise vigorously for brief (~5 min) periods before consuming a standard-size meal (Francois et al, 2014). Interestingly, these routines were found to improve glucose homeostasis more than isoenergetic regimens comprised of traditional feeding and exercise patterns.…”
Section: Strategies For Decongestionmentioning
confidence: 99%
“…Thus, approaches targeting the cause rather than the symptoms of nutrient overload should yield more desirable outcomes. Moving beyond the standard recommendation to “eat less and move more,” recent studies employing unconventional behavior modification interventions have produced intriguing results, including intermittent fasting regimens in which rodents or human subjects fast for extended periods followed by ad libitum eating (Azevedo et al, 2013; Trepanowski et al, 2011), as well as “exercise snacking” regimens in which individuals exercise vigorously for brief (~5 min) periods before consuming a standard-size meal (Francois et al, 2014). Interestingly, these routines were found to improve glucose homeostasis more than isoenergetic regimens comprised of traditional feeding and exercise patterns.…”
Section: Strategies For Decongestionmentioning
confidence: 99%
“…Like other calorie restriction (CR) or fasting regimens [8,10,11,[31][32][33], all of which could cause changes in markers (ketone bodies, and glucose) that were similar to those caused by absolute fasting. All of the subjects self-described slight or tolerable hunger sensation and slight fatigue, besides, high dietary adherence during the one-week FF operation, indicated that FF regimen is an acceptable manner in normal life for short-term survival by using the body fat and glycogen other than the ) and Actinobacteria (p=0.046) and Verrucomicrobia (p=0.01) increased at 1W group.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados obtidos na presente investigação, em concordância com outros estudos 6,11,16,20,21 revelaram que os sujeitos entrevistados percebem a relevância do tema obesidade juvenil nos dias atuais, e ressaltam a importância da adequação da composição corporal ao percentil para a faixa etária no sentido de se evitar doenças relacionadas.…”
Section: Discussionunclassified